RANCANG BANGUN APLIKASI PLOTING JADWAL MATA KULIAH PADA FAKULTAS TEKNIK UNIVERSITAS MAJALENGKA - Dzulfikri Alkautsari (PROCEEDING STIMA)
Course schedules are one of the important components in the successful implementation of teaching and learning activities in universities because all lecturer and student activities depend on the schedule, so the schedule must be arranged correctly at the beginning of the semester. The preparation of the course schedule by using a spreadsheet application manually, as was done at the Majalengka University Faculty of Engineering, requires high accuracy because it must pay attention to the constraints in scheduling (room, lecturer, student class, day and time) so that no clashes occur. Problems in preparing the schedule can be solved using a schedule plotting application that can generate schedules automatically using genetic algorithms and using GUI (Graphical User Interface). The schedule plotting application generated in the Job Training research has been successfully tested to schedule courses in the Informatics Engineering Study Program of the Faculty of Engineering, Majalengka University.